Analysis of the results of the study of sound pronunciation in patients with prosthetics with complete removable dentures - Mykhailo Nidzelskyi (Kazimierz Wielki University, 2024)
Introduction. One of the most important social tasks is protection and strengthening people's health. In the modern world, there is a trend towards aging of the population, which causes a general increase in morbidity. This provision fully refers to the deterioration of the dental status of the population, which leads to an increase in the number of patients who have defects of the dentition. The complete loss of teeth causes particularly significant morphological, functional and aesthetic changes in the maxillofacial area. In dental practice, the prosthetics of fixed prosthetics is widely used. Restoration of speech is one of the main tasks when using removable dentures.             The aim of the study: to research the peculiarities of the development of speech adaptation when using removable dentures of a long length. Materials and methods. For research, 2 groups of patients were formed: the first group of patients without dental defects rows, the second group - with defects of tooth rows. The research was conducted using the sound computer spectography method before prosthetics, immediately after fixation of orthopedic structures, after 3, 7, 30 days. Results. The application of the sound computer spectrography method made it possible to carry out a graphic registration of the pronunciation of the sounds of the Ukrainian language by patients before prosthetics and during adaptation to orthopedic structures. The obtained results demonstrate qualitative differences between sound pronunciation in pathients without dentition defects (control) and patients with partial loss of teeth. They also reveal the existence of certain dynamics of acoustic processes during the first 30 days of using fixed structures. Conclusion. Thus, with excessive occlusal contacts of the teeth, the power and frequency of loudest sounds is significantly reduced. When manufacturing non-removable structures using the digital method, adaptation is faster compared to the analog method. At the beginning of using non-removable structures, after 3 days the power of sounds [o], [u] and the frequency of sounds [a], [o] are restored. After a temporary new deviation from the norm after 7 days, the frequency and power of loud sounds are fully restored after 30 days.